Early social interaction : a case comparison of developmental pragmatics and psychoanalytic theory - Forrester, Michael A. (Cambridge : Cambridge University Press, 2015)
'When a young child begins to engage in everyday interaction, she has to acquire competencies that allow her to be oriented to the conventions that inform talk-in-interaction and, at the same time, deal with emotional or affective dimensions of experience. The theoretical positions associated with these domains - social action and emotion - provide very different accounts of human development and this book examines why this is the case. Through a longitudinal video-recorded study of one child learning how to talk, Michael Forrester develops proposals that rest upon a comparison of two perspectives on everyday parent-child interaction taken from the same data corpus - one informed by conversation analysis and ethnomethodology, the other by psychoanalytic developmental psychology. Ultimately, what is significant for attaining membership within any culture is gradually being able to display an orientation towards both domains - doing and feeling, or social action and affect'--
'This book brings together various threads of the research work I've been involved with over a number of years. This research is based on a longitudinal video-recorded study of one of my daughters as she was learning how to talk. The impetus for engaging in this work arose from a sense that within developmental psychology and child language, when people are interested in understanding how children use language, they seem over-focused or concerned with questions of formal grammar and semantics. My interest is on understanding how a child learns to talk and through this process is then understood as being or becoming a member of a culture'--
Introduction -- Developmental pragmatics and conversation analysis -- Child-focused conversation analysis -- A psychoanalytic reading of early social relations -- Repression and displacement in everyday talk-in-interaction -- Research practices and methodological objects -- Learning how to repair -- Learning what not to say: repression and interactive vertigo -- A question of answering -- Interaction and the transitional space -- Self-positioning, membership and participation -- Discourses of the self and early social relations -- Social practice and psychological affect.
Includes bibliographical references (pages 270-281) and index.
Keywords: Social interaction; Child development; Parent and child